Empowering Financial Literacy from an Early Age: A Community Service onSaving Awareness (GEMBUNG) for Elementary School Children in WangkelangVillage - Isnaini, Tamimatul (Faculty of Economics and Islamic Business State Islamic University of Palangka Raya, 2025)
The purpose of socializing saving from an early age to elementary school children is to provide children with an understanding of simple financial management and provide education on the importance of saving from an early age. The method of activity carried out in this activity is by socializing the delivery of material offline or face to face. The objects of this activity are children in Wangkelang Village who are in the age range of 2 to 12 years with a total of 20 children. The result of this dedication is that socialization activities can run smoothly, namely facilities that support and enthusiasm from the Wangkelang Village Elementary School children during the activity. The material presented is acceptable and well understood. There are some children who are already enthusiastic about putting the remaining pocket money into the piggy bank.